A depleted mantle source for Neoproterozoic continental rifting in the Seve Nappe Complex, Kebnekaise region, northern Swedish Caledonides - Callegari, Riccardo; Barker, Abigail K.; Barnes, Christopher J.; Walczak, Katarzyna; Ziemniak, Grzegorz; Klonowska, Iwona; Kooijman, Ellen; Rousku, Sabine; Kośmińska, Karolina; Majka, Jarosław (Frontiers in Earth Science, 2024)
The Central Iapetus Magmatic Province (CIMP) is a large igneous province (LIP) emplaced in the Baltican and Laurentian paleocontinents that marks the onset of the Caledonian Wilson Cycle. Paleozoic magmatism of the CIMP is preserved in both northeastern America and northern Europe. This study investigates rocks belonging to the hyper-extended margin of Baltica currently found in the Seve Nappe Complex of the Scandinavian Caledonides. Specifically, U-Pb zircon geochronology and whole-rock geochemistry are applied to a migmatitic variety of the Vierručohkka amphibolite of the Mårma Terrane, to the Aurek gabbro, and amphibolite of the Aurek Assemblage exposed in the Seve Nappe Complex in the Kebnekaise region, northern Swedish Caledonides. U-Pb zircon geochronology yields crystallization ages of 626 ± 7 Ma for the protolith of the Vierručohkka amphibolite, and 614 ± 2 Ma and 609 ± 1 Ma for the emplacement of the Aurek gabbro and amphibolite protolith, respectively. A younger age of 599 ± 3 Ma is recorded in the Vierručohkka amphibolite and is interpreted as the age of partial melting and migmatization. The geochemical signatures of the rocks demonstrate crustal assimilation during the emplacement of their protoliths and modification due to prograde metamorphic processes during Caledonian subduction. The Vierručohkka amphibolite and the Aurek Assemblage samples display upper and lower crustal assimilation, respectively. Trace elements (Dy, Sm, Lu, and Y) record the growth of metamorphic garnet, while elevated TiO2 contents record the crystallization of metamorphic rutile. Nevertheless, high field strength elements (HSFE) and ∆Nb suggest a depleted mantle source for the magmas of the protoliths of the investigated rocks. Altogether, geochemical data indicate that the igneous activity recorded in the Vierručohkka amphibolite and the Aurek Assemblage between c. 626-609 Ma is related to continental rifting processes associated with the opening of the Iapetus Ocean.